Relationship between Community Empowerment Strategy by Management and Participation of PKK Women in Nagari Tanjung Beringin, Pasaman Regency - Lastri, Nopita; Azizah, Zahratul (Universitas Negeri Padang, 2023)
The aim of this research is to find out the picture and also the relationship between empowerment strategies by administrators and the participation of PKK women in Nagari Tanjung Beringin, Pasaman Regency. This research uses a correlational quantitative approach. The population of this study is all PKK mothers registered with the PKK in 2022/2023 in Nagari Tanjung Beringin, Pasaman Regency, totaling 30 people. The sampling technique in this research was carried out using the total sampling method, so the total sample that the researchers took was 30 PKK women in Nagari Tanjung Beringin, Pasaman Regency. The data collection technique uses a questionnaire format and a list of statements as a data collection tool, the data analysis technique uses percentages to find correlations using the product moment formula. The results of this research are: 1.) The community empowerment strategy used by administrators in Nagari Tanjung Beringin, Pasaman Regency shows that respondents chose the alternative answer strongly agree (SS) 24.1%, chose the alternative answer always (S) 64.4%, alternative answers disagree (KS) 5.9%, and those who chose the alternative answer disagree (TS) 5.6%. This means that the community empowerment strategy used by the administrators in Nagari Tanjung Beringin, Pasaman Regency can be said to be very good and can increase the activities of PKK women in empowering the community. 2.) The participation of PKK women in Nagari Tanjung Beringin, Pasaman Regency shows that respondents chose alternative answers. strongly agree (SS) 27.6%, choose the alternative answer always (S) 61.3%, alternative answer do not agree (KS) 5.6%, and those who choose the alternative answer disagree (TS) 5.6%. This means that the participation of PKK women in Nagari Tanjung Beringin, Pasaman Regency can be said to be very good and can improve empowerment strategies in empowering the community and 3.) Product moment correlation data analysis carried out obtained r count = 1.935 and this value was consulted with r table = 0.361 with N = 30. From the results of the consultation, it was found that r count > r table if based on the 5% confidence level, namely 0.361. If r calculated is greater than r table then Ho is rejected and conversely Ha is accepted. So, the conclusion is that there is a significant relationship between empowerment strategies by administrators and the participation of PKK women in Nagari Tanjung Beringin, Pasaman Regency.